Answer

Verified

441.9k+ views

Hint: Assume the numbers as (a – d), a, (a + d) and apply the conditions to solve to get the values of ‘a’ and ‘d’ and after that put that values in assumed numbers to get the answer.

Complete step-by-step answer:

As we have given that the three numbers are in A.P. and therefore we will assume (a-d), a, (a+d) as the three numbers in A.P. with ‘a’ as the first term and‘d’ is the common difference.

As the sum of three numbers is 12, therefore we can write,

(a - d) + a + (a + d) = 12

$\Rightarrow $a - d + a + a + d = 12

$\Rightarrow $a + a + a = 12

$\Rightarrow $ 3a = 12

$\Rightarrow a=\dfrac{12}{3}$

$\Rightarrow $ a = 4 …………………………………. (2)

Now, as per the second condition given in the problem we can write,

$\therefore {{\left( a-d \right)}^{3}}+{{a}^{3}}+{{\left( a+d \right)}^{3}}=408$

If we put the value equation (2) in the middle term of the above equation we will get,

$\Rightarrow {{\left( a-d \right)}^{3}}+{{4}^{3}}+{{\left( a+d \right)}^{3}}=408$

$\Rightarrow {{\left( a-d \right)}^{3}}+64+{{\left( a+d \right)}^{3}}=408$

$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=408-64$

$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ ………………………………… (3)

Now to proceed further in the solution we should know the formula given below,

Formula:

\[\left( {{x}^{3}}+{{y}^{3}} \right)=\left( x+y \right)\times \left( {{x}^{2}}+{{y}^{2}}-xy \right)\]

By using above formula we can write equation (3) as follows,

\[\therefore \left[ \left( a-d \right)+\left( a+d \right) \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]

\[\therefore \left[ a-d+a+d \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]

\[\therefore \left[ a+a \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}+ad-ad-{{d}^{2}} \right) \right]=344\]

\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}-{{d}^{2}} \right) \right]=344\]

\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]

Now to proceed further we should know the formulae given below,

Formulae:

\[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}+2xy+{{y}^{2}} \right)\] And \[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}-2xy+{{y}^{2}} \right)\]

By using the above formulae we can write the above equation as,

\[\therefore 2a\times \left[ \left( {{a}^{2}}-2ad+{{d}^{2}} \right)+\left( {{a}^{2}}+2ad+{{d}^{2}} \right)-{{a}^{2}}+{{d}^{2}} \right]=344\]

By opening the brackets we will get,

\[\Rightarrow 2a\times \left[ {{a}^{2}}-2ad+{{d}^{2}}+{{a}^{2}}+2ad+{{d}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]

\[\Rightarrow 2a\times \left[ {{d}^{2}}+{{a}^{2}}+{{d}^{2}}+{{d}^{2}} \right]=344\]

\[\Rightarrow 2a\times \left[ 3{{d}^{2}}+{{a}^{2}} \right]=344\]

By substituting the value of equation (2) in the above equation we will get,

\[\Rightarrow 2\times 4\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]

\[\Rightarrow 8\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]

\[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]

\[\Rightarrow 3{{d}^{2}}+16=43\]

\[\Rightarrow 3{{d}^{2}}=43-16\]

\[\Rightarrow 3{{d}^{2}}=27\]

\[\Rightarrow {{d}^{2}}=\dfrac{27}{3}\]

\[\Rightarrow {{d}^{2}}=9\]

By taking square roots on both sides of the equation we will get,

\[\therefore d=\pm 3\]

Therefore d = 3 OR d = -3 ……………………………………. (4)

Now we will rewrite the three numbers below,

(a – d), a, (a + d)

If we put the values of equation (2) and equation (4) in above equation as shown below,

a = 4 and d = 3

Therefore numbers will become,

(4 – 3), 4, (4+3)

Therefore the numbers are,

1, 4, 7.

Now,

a = 4 and d = - 3

Therefore numbers will become,

[4 – (-3)], 4, [4+(-3)]

(4 + 3), 4, (4 – 3)

Therefore the numbers are,

7, 4, 1.

Therefore the three numbers are 1, 4, 7 or 7, 4, 1.

Note: Assume the standard numbers given by (a – d), a, (a + d) to make the calculations easier. Also in the step ${{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ you can also use the formulae of \[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]

Complete step-by-step answer:

As we have given that the three numbers are in A.P. and therefore we will assume (a-d), a, (a+d) as the three numbers in A.P. with ‘a’ as the first term and‘d’ is the common difference.

As the sum of three numbers is 12, therefore we can write,

(a - d) + a + (a + d) = 12

$\Rightarrow $a - d + a + a + d = 12

$\Rightarrow $a + a + a = 12

$\Rightarrow $ 3a = 12

$\Rightarrow a=\dfrac{12}{3}$

$\Rightarrow $ a = 4 …………………………………. (2)

Now, as per the second condition given in the problem we can write,

$\therefore {{\left( a-d \right)}^{3}}+{{a}^{3}}+{{\left( a+d \right)}^{3}}=408$

If we put the value equation (2) in the middle term of the above equation we will get,

$\Rightarrow {{\left( a-d \right)}^{3}}+{{4}^{3}}+{{\left( a+d \right)}^{3}}=408$

$\Rightarrow {{\left( a-d \right)}^{3}}+64+{{\left( a+d \right)}^{3}}=408$

$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=408-64$

$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ ………………………………… (3)

Now to proceed further in the solution we should know the formula given below,

Formula:

\[\left( {{x}^{3}}+{{y}^{3}} \right)=\left( x+y \right)\times \left( {{x}^{2}}+{{y}^{2}}-xy \right)\]

By using above formula we can write equation (3) as follows,

\[\therefore \left[ \left( a-d \right)+\left( a+d \right) \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]

\[\therefore \left[ a-d+a+d \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]

\[\therefore \left[ a+a \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}+ad-ad-{{d}^{2}} \right) \right]=344\]

\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}-{{d}^{2}} \right) \right]=344\]

\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]

Now to proceed further we should know the formulae given below,

Formulae:

\[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}+2xy+{{y}^{2}} \right)\] And \[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}-2xy+{{y}^{2}} \right)\]

By using the above formulae we can write the above equation as,

\[\therefore 2a\times \left[ \left( {{a}^{2}}-2ad+{{d}^{2}} \right)+\left( {{a}^{2}}+2ad+{{d}^{2}} \right)-{{a}^{2}}+{{d}^{2}} \right]=344\]

By opening the brackets we will get,

\[\Rightarrow 2a\times \left[ {{a}^{2}}-2ad+{{d}^{2}}+{{a}^{2}}+2ad+{{d}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]

\[\Rightarrow 2a\times \left[ {{d}^{2}}+{{a}^{2}}+{{d}^{2}}+{{d}^{2}} \right]=344\]

\[\Rightarrow 2a\times \left[ 3{{d}^{2}}+{{a}^{2}} \right]=344\]

By substituting the value of equation (2) in the above equation we will get,

\[\Rightarrow 2\times 4\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]

\[\Rightarrow 8\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]

\[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]

\[\Rightarrow 3{{d}^{2}}+16=43\]

\[\Rightarrow 3{{d}^{2}}=43-16\]

\[\Rightarrow 3{{d}^{2}}=27\]

\[\Rightarrow {{d}^{2}}=\dfrac{27}{3}\]

\[\Rightarrow {{d}^{2}}=9\]

By taking square roots on both sides of the equation we will get,

\[\therefore d=\pm 3\]

Therefore d = 3 OR d = -3 ……………………………………. (4)

Now we will rewrite the three numbers below,

(a – d), a, (a + d)

If we put the values of equation (2) and equation (4) in above equation as shown below,

a = 4 and d = 3

Therefore numbers will become,

(4 – 3), 4, (4+3)

Therefore the numbers are,

1, 4, 7.

Now,

a = 4 and d = - 3

Therefore numbers will become,

[4 – (-3)], 4, [4+(-3)]

(4 + 3), 4, (4 – 3)

Therefore the numbers are,

7, 4, 1.

Therefore the three numbers are 1, 4, 7 or 7, 4, 1.

Note: Assume the standard numbers given by (a – d), a, (a + d) to make the calculations easier. Also in the step ${{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ you can also use the formulae of \[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]

Recently Updated Pages

Cryolite and fluorspar are mixed with Al2O3 during class 11 chemistry CBSE

Select the smallest atom A F B Cl C Br D I class 11 chemistry CBSE

The best reagent to convert pent 3 en 2 ol and pent class 11 chemistry CBSE

Reverse process of sublimation is aFusion bCondensation class 11 chemistry CBSE

The best and latest technique for isolation purification class 11 chemistry CBSE

Hydrochloric acid is a Strong acid b Weak acid c Strong class 11 chemistry CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Name 10 Living and Non living things class 9 biology CBSE

The Buddhist universities of Nalanda and Vikramshila class 7 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE